Corrosion inhibition of mild steel in 15 wt% HCl solution by synthetic and green compounds - Ajayi, Olorunfemi Michael (2019)
Registration, Evaluation, Authorization, and restriction of CHemicals (REACH) legislation, in conjunction with Paris Commission (PARCOM) recommendations (1991), are driving research into environmentally friendly alternatives to currently-used corrosion inhibitors. The main focus of this thesis is on compounds of plant-origin because they contain components which can be extracted by simple procedures. These plant extracts are relatively benign in their environmental impact compared to the highly toxic compounds, including propargyl alcohol (PA) and 2- mercaptobenzimidazole (MI), which are currently in use to mitigate the corrosion of oil and gas wells during acidizing treatment. The four ‘green’ corrosion inhibitors, chosen for this research, were extracts from durum wheat (DW), aloe vera gel (AV), inulin (IN; extracted from Jerusalem artichoke), and broccoli (BC). The corrosion inhibition performance of PA, MI, DW, BC, IN and AV for mild steel (MS), immersed in 15wt% HCl solution in the absence and presence of the inhibitors, has been investigated. Weight loss and electrochemical (open circuit potential (OCP), potentiodynamic polarization and linear polarization resistance) were used to determine the corrosion inhibition performance of the inhibitors with a variation of concentration of the inhibitors, solution temperature (20-60°C) and immersion time (5- 192 h). Also, gas chromatography-mass spectrometry (GC- MS) and Fourier transform infrared (FTIR) spectroscopy were further employed to characterize all the chemical compounds to determine their main constituents and functional groups. The as-received MS surfaces were analyzed after immersion in uninhibited and inhibited solutions using scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and 3D profilometry. X-ray photoelectron spectroscopy (XPS) was performed to determine the nature and composition of the protective film formed at the MS/HCl solution interface.